Suppose i + h - 2*h = 8, -29 = -4*i + 3*h. Let v = i + -3. Solve 0*a + v*a = -6 for a.
-3
Suppose 2*x + 2 = -5*i, 3*x = 5*i - i + 20. Solve x*b - 3*b = 0 for b.
0
Let l = -35 - -45. Solve -l = w + 4*w for w.
-2
Let v(s) be the first derivative of -s4⁄4 + 2*s3⁄3 + s + 3. Let u be v(-2). Solve 5*k = -7 + u for k.
2
Suppose 0 = i - 0*i + 4*w - 20, 0 = 2*i + 5*w - 46. Suppose -a + 4*o = -i, -3*a + 18 = -2*a - 2*o. Solve a + 2 = 5*k for k.
2
Let q = -26 + 30. Solve 5 = -q*c - c for c.
-1
Let p© = c + 3. Let l be 0/(-4 + 3)*1. Let w be p(l). Solve w + 3 = -3*r for r.
-2
Let f(w) be the third derivative of -w4⁄24 - w3⁄3 - 3*w**2. Let z be f(-2). Solve -c + 3*c = z for c.
0
Let d = -3 - -5. Let t = -2 + 4. Suppose 2*n = 4*n - 6, n - 25 = -t*y. Solve -d*p - 1 = -y for p.
5
Let i be 2/(-11) + (-204)/(-33). Solve 0 = -4*x - i - 2 for x.
-2